2022
DOI: 10.1001/jamanetworkopen.2022.6257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plasma and Blood Donations on Levels of Perfluoroalkyl and Polyfluoroalkyl Substances in Firefighters in Australia

Abstract: IMPORTANCEElevated levels of blood perfluoroalkyl and polyfluoroalkyl substances (PFASs) have been associated with a range of adverse health outcomes. Firefighters have been exposed to PFASs in firefighting foams and have previously been shown to have higher PFAS levels in blood samples than the general population. No interventions have been shown to reduce PFAS levels. OBJECTIVE To examine the effect of blood or plasma donations on PFAS levels in firefighters in Australia. DESIGN, SETTING, AND PARTICIPANTS Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Three controlled experimental studies (and one registration [42]) examined the effect of iron supplementation [20], donation frequency [27, 42] or collection programme [16] on donor health with a follow‐up period of 1–6 months. Finally, two studies had a longer follow‐up period (6–12 months), comparing whole blood donations, plasma donations and observation only [15], or different donation volumes [26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three controlled experimental studies (and one registration [42]) examined the effect of iron supplementation [20], donation frequency [27, 42] or collection programme [16] on donor health with a follow‐up period of 1–6 months. Finally, two studies had a longer follow‐up period (6–12 months), comparing whole blood donations, plasma donations and observation only [15], or different donation volumes [26].…”
Section: Resultsmentioning
confidence: 99%
“…Two full texts could not be retrieved [10,11]. To avoid duplication of studies, the protocol [12] and two of the registrations [13,14] of studies that are described by identified research articles [15,16] are not included in our summary. The remaining 94 research articles and 5 registrations are described below.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, firefighters have been exposed to harmful chemicals from fire smoke and firefighting foams containing high levels of various PAHs and PFAS (Jalilian et al, 2019;Gasiorowski et al, 2022). Additionally, a new concern has been raised regarding firefighters' exposure to PFAS through turnout gear.…”
Section: Pfas In Blood Serummentioning
confidence: 99%
“…Several studies have observed the association between PFAS exposure and a range of adverse health outcomes (Graber et al, 2021). Although PFAS are potentially harmful to human health, the exact threshold at which these risks may increase has remained unknown (Gasiorowski et al, 2022). Like other chemical substances, their ability to produce adverse health effects depends on exposure circumstances, such as magnitude, duration, and route of exposure (Fenton et al, 2021).…”
Section: Pfas In Blood Serummentioning
confidence: 99%